Examination and counseling of gynecological cases during Corona Virus Disease 2019 (COVID-19) pandemic - I Gde Sastra Winata; Clara Amanda (Universitas Airlangga, 2021)
HIGHLIGHTS1. Clinical gynecology examinations must adapt to pandemic situation.2. It must pay attention to universal precautions, aseptic and sterile technique to minimize infection transmission.3. In terms of reducing contact, the need for examination are divided by priority into